Annuity payments can increase patient access to innovative cell and gene therapies under England’s net budget impact test - Jesper Jørgensen; Panos Kefalas (Journal of Market Access & Health Policy)
Background: Cell and gene therapies have the potential to provide therapeutic breakthroughs, but the high costs of researching, developing, manufacturing and delivering them translate into prices that may challenge healthcare budgets. Various measures exist that aim to address the affordability challenge, including reducing price, limiting patient numbers and/or linking remuneration to product performance. Objective: To explore how the net budget impact test recently introduced in England can affect patient access to high-value, one-off cell and gene therapies, and how managed entry agreements can improve access. Methods: We use a hypothetical example where a new high-value, one-off therapy launches in an indication where it displaces a relatively low cost chronic treatment. We calculate the number of patients that can be treated without exceeding the £20 million net budget impact threshold, and compare results for scenarios where a full upfront payment is used, and where annuity-based payments are used. Results: Charging a full upfront payment at the time of treatment can lead to suboptimal patient access. Conclusion: Annuity-based payments in combination with an outcomes-based remuneration scheme reduce consequences of decision uncertainty and can increase patient access, without exceeding the net budget impact test.